2007
DOI: 10.1007/s11434-007-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gravity on narrow input forced drainage in 2D liquid foams

Abstract: Liquid foam is a dense packing of gas bubbles in a small amount of liquid containing surfactants or other surface-active macromolecules, which is one of the highly organized materials and possesses hallmark rheological behaviour of soft matters. Forced foam drainage is the flow of constantly inputted liquid through the network of interstitial channels between bubbles under actions of gravity and capillarity. This process involves two mechanisms: minimal viscous flow dissipation of liquid and minimal surface en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…To quantify the extremum tendencies of viscous dissipation and surface energy, different criteria have been tested in different cases (Ge et al, 2006a;Sun et al, 2007) with preliminary success. In this section, we will focus on a somewhat idealized case of nano gas-liquid flow as described in Fig.…”
Section: Dominant Mechanisms and Stability Conditionmentioning
confidence: 99%
“…To quantify the extremum tendencies of viscous dissipation and surface energy, different criteria have been tested in different cases (Ge et al, 2006a;Sun et al, 2007) with preliminary success. In this section, we will focus on a somewhat idealized case of nano gas-liquid flow as described in Fig.…”
Section: Dominant Mechanisms and Stability Conditionmentioning
confidence: 99%
“…The influence of gravity on narrow input forced drainage in 2D liquid foams were numerically studied [9] , and we found that both gravitational and horizontal wave-front positions could be well described with power laws of time as gravity ranges from g = 9.8 m/s 2 to zero. Generally, the propagation of the forced drainage wave with single input has been studied clearly [10] .…”
mentioning
confidence: 95%